The Silent Invader : a Rare Case of Invasive Mole - Katakdhond, Shriraj; Dhedia, Radhika Ashok; Pojala, Ramyapriya; Patel, Shivani; Saha, Shrestha (Journal of Neonatal Surgery, 2025)
Invasive mole is a highly vascular subset of gestational trophoblastic disease. We report a case of Invasive Mole which presented as abnormal intermenstrual uterine bleeding in a middle-aged female. Based on clinical, radiological, and lab findings diagnosis of Invasive Mole was made. Despite adequate medical management symptoms persisted hence Total abdominal hysterectomy with Bilateral salpingectomy was done. In view of young age of patient both ovaries were preserved. Post operatively β-hCG levels were monitored till 6 months after 2 consecutive undetectable value